Portfolio Theory, Asset Demand and Taxation: Comparative Statics with Many Assets - Sandmo, Agnar (Review of Economic Studies, 1977)
Journal Article Portfolio Theory, Asset Demand and Taxation: Comparative Statics with Many Assets Get access Agnar Sandmo Agnar Sandmo Norwegian School of Economics and Business Administration, Bergen Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 2, June 1977, Pages 369–379, https://doi.org/10.2307/2297074 Published: 01 June 1977